The impact of food price shocks on weight loss: Evidence from the adult population of Tanzania - Sol García-Germán; Alessandro Romeo; Emiliano Magrini; Jean Balié (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2016)
Undernourishment is still widespread in Tanzania, while obesity is becoming an issue of magnitude similar to undernutrition in the country. In this paper we examined the impact of an increase in maize prices on the nutritional status of Tanzania's adult population. We found that undernutrition increases as a result of increased prices, while the overweight and obese decrease their energy intake. The study presents evidences of the so called early stage of the nutritional transition that characterize developing countries. All in all, these findings are suggestive of the fact that food price shocks should be taken into consideration when designing policy and programmes aiming at addressing malnutrition in low income countries.
Keywords: C31; D12; D13; I31; Q18; 330; food price shocks; food demand models; malnutrition; Tanzania